2019
DOI: 10.3390/su11113141
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Continuous Intention on Food Delivery Apps: Extending UTAUT2 with Information Quality

Abstract: This study empirically analyzes an extended Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model that augments information quality to identify the determinants of continuous use intention for food delivery software applications. A sample survey of 340 respondents who had ordered or purchased food through delivery apps was used for the analysis. The results indicate that habit had the strongest influence on continuous use intention, followed by performance expectancy and social influence. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
299
1
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(346 citation statements)
references
References 66 publications
28
299
1
18
Order By: Relevance
“…Meanwhile, with the advancement of information technology and constant improvisation of smartphones, users now face fewer hurdles in using them. Therefore, our findings were consistent with the results of Lee and Sung [17], who noticed a non-significant impact of effort expectancy on CUI for food delivery apps. Social influence was another non-determinant factor in our study and was in accordance with the previous study of Hew and Lee [81].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Meanwhile, with the advancement of information technology and constant improvisation of smartphones, users now face fewer hurdles in using them. Therefore, our findings were consistent with the results of Lee and Sung [17], who noticed a non-significant impact of effort expectancy on CUI for food delivery apps. Social influence was another non-determinant factor in our study and was in accordance with the previous study of Hew and Lee [81].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it can be deduced that the continuous intention to use mobile news apps is influenced by the users' perceived usefulness of the app, along with habit, hedonic motivation, and facilitating conditions. These findings partially corroborate the findings of previous studies [17,31,96] and substantiate that users place equal importance on the cognitive benefits of reducing time and effort, along with intrinsic utilities like hedonic motivation, in addition to habit and facilitating conditions when using mobile news apps.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study adopts the construct "price value," from UTAUT-2, which is restructured as "cost-saving efficiency" or CSE. This has resulted in variances of WTPM (R 2 = 0.29) and an intention to repurchase (R2 = 0.58), being significant enhanced compared to previous study on UTAUT-2 in the online shopping context [32,33,40,111,112]. Overall, our study confirmed the important roles of delivery efficiency, cost-saving efficiency, and shopping experience in influencing online shopping and in UTAUT-2.…”
Section: Discussionsupporting
confidence: 71%
“…Considering that the Korean-style grocerant model is still in its infancy, the findings of this study may be inappropriate to apply to non-Korean countries. Second, the steadily increasing number of single-person households accounted for 28.6% of all households in 2017 [58]. This makes it necessary to analyze the intergroup differences between single-person and multiple-person households.…”
Section: Limitations and Future Researchmentioning
confidence: 99%